Progress Towards Gender Equality in the Middle East and North Africa Region - World Bank (Washington, DC, 2017)
Progress towards gender equality in the Middle East and North Africa (MNA) region is a descriptive note on progress and gaps towards gender equality and women’s empowerment in the region, produced to provide the situational context to the World Bank Group’s regional gender action plan (RGAP) FY18-23. It shows that the MNA region has made considerable gains in women’s access to education and health, and identifies persistent challenges that remain. Specifically, gaps need to be addressed in the areas of women’s economic opportunities (labor force participation, financial inclusion), women’s voice and agency (political participation, gender based violence, etc.), and gender specific vulnerabilities in conflict and fragility, as well as women’s participation in reconstruction efforts. In addition, the note shows that development outcomes are correlated with the larger issue of norms and stereotypes related to women’s role in society, another area in which MNA lags behind other regions.